ANALISIS GAYA KOGNITIF SISWA DENGAN HASIL BELAJAR EKONOMI PEMINATAN DI SMAN 2 PONTIANAK - Asmorosari, Devi Udia (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
Abstract This research is about the cognitive style of students with their learning outcomes in the subject of economic interest which is motivated by the lack of attention to the different characteristics of each learner which will affect the learning outcomes. This study aims to determine the cognitive style of students with learning outcomes in economic subjects in the interest of class XII IIS SMA Negeri 2 Pontianak. This research uses qualitative approach and descriptive research form. Sources of data in this study are the students of class XII IIS 4, amounting to 39 students and a teacher subjects economic subjects of interest. Data were collected using interview guidance instruments and observation sheets. The results show that FD students have the highest score of 84.00 with excellent predicate, FI students have the highest score of 91.50 with excellent predicate, the more dominant students tend to have cognitive style of field dependent and who have independent cognitive style field have more learning outcomes Better than students who have cognitive style field dependent on economic subjects of interest. Keywords: Field dependent, field independent, learning outcomes